Caracterización de la festividad del Pawkar Raymi como manifestación cultural de la parroquia Veintimilla, cantón Guaranda, provincia Bolívar. Año 2023 - Chimbolema Avilés, María Dolores (2023)
The Pawkar Raymi festivity in Veintimilla Parish, Guaranda Canton, Bolivar Province, is an ancestral celebration that reflects the cultural identity of the community, honoring the flowering season and thanking Pachamama for her generous resources. This thesis seeks to characterize the Pawkar Raymi as a cultural manifestation of the Veintimilla Parish, investigating its historical origins, symbolic and ritual aspects, and its evolution over time. In addition, the influence of the festivity on the daily life, social cohesion, and economic and tourism development of the community will be analyzed. To address this objective, methodologies and techniques such as literature review, participant observation, and interviews and surveys of community members, local leaders and visitors will be used. The characterization of the Pawkar Raymi will allow a greater knowledge and appreciation of this tradition, fostering its preservation and promotion at the local, national and international levels. This research will contribute to the strengthening of the cultural identity and sustainable development of Veintimilla, highlighting the tourism and educational potential of this authenticcelebration. Keywords: Cultural Identity, Pawkar Raymi, Community, Development, Logical Framework, Tourism, Cultural Manifestation, Rural Tourism, Cultural Expression, Tourism Promotion.